2019
DOI: 10.1186/s12913-019-4477-3
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating commissioning pathways for the successful implementation of innovative health technology in primary care

Abstract: Background Commissioning innovative health technologies is typically complex and multi-faceted. Drawing on the negotiated order perspective, we explore the process by which commissioning organisations make their decisions to commission innovative health technologies. The empirical backdrop to this discussion is provided by a case study exploring the commissioning considerations for a new photoplethysmography-based diagnostic technology for peripheral arterial disease in primary care in the UK. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In NHS England, there is no direct connection between the DTAC or ESH frameworks certification and reimbursement. A positive endorsement from NICE can support the acceptance and adoption of the health app by providers and Clinical Commissioning Groups (CCGs) ( 25 ). CCGs are primary care-led groups that include the GP groups in a particular area and represent statutory NHS bodies responsible for the planning and commissioning of health care services for their area, that might provide reimbursement for a digital technology depending on their strategy.…”
Section: Resultsmentioning
confidence: 99%
“…In NHS England, there is no direct connection between the DTAC or ESH frameworks certification and reimbursement. A positive endorsement from NICE can support the acceptance and adoption of the health app by providers and Clinical Commissioning Groups (CCGs) ( 25 ). CCGs are primary care-led groups that include the GP groups in a particular area and represent statutory NHS bodies responsible for the planning and commissioning of health care services for their area, that might provide reimbursement for a digital technology depending on their strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Uniquely, we have shown that evidence is not used solely as a source of information by commissioners, but also as a tool to effect change and stimulate improvements, as well as a warrant for convincing others and justifying decision-making. Overall, the commissioning of healthcare services and the related contexts is an understudied topic, [ 1 , 50 ] and we believe have made a new contribution to the literature by applying the analytical lens of a realist evaluation to this topic.…”
Section: Discussionmentioning
confidence: 99%
“…NHS primary care commissioning involves the planning, contracting, and monitoring of primary care services (GP, dentistry, pharmacy, and ophthalmology services) [ 1 , 2 ]. Although the NHS has a documented ‘commissioning cycle’ consisting of nine discrete steps and activities, [ 3 ] in practice, commissioning is ‘messy and fragmented,’ [ 4 ] and only some activities undertaken by commissioners overlap with the official nine-step ‘commissioning cycle’ [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the United Kingdom, the analysis and commissioning of the decision-making process so that public services are planned and contracted in order to meet unique needs, focused on innovative health technologies, specifically that of diagnostic innovation for the treatment of vascular disease in PHC. The results show that decisions are subject to the micro-policies of the organizational environment, competing agendas, interests, priorities, demands and personal inclinations to be persuasive and convincing, instead of adopting a simple technical rationality 34 .…”
Section: /21mentioning
confidence: 97%